Increasing Students’ Vocabulary Using Fairy Tales at SMKN 6 Makassar - Nur Asfira Suhardi; Andi Muliati; Geminastiti Sakkir; Joseph Agbuya Villarama (Journal of Language Learning and Assessment, 2023)
Purpose This research was a pre-experimental study with one group pre-tests and a post-test design, which aims to determine the effectiveness of reading fairy tales to increase the vocabulary of class XI Culinary 1 UPT SMKN 6 Makassar students. Methodology The sample in this study was 30 students using the cluster random sampling technique. This research used a vocabulary test as a data collection instrument. Results/Findings The results of this test were used to the effectiveness of the method of reading fairy tales to increase the vocabulary of class XI UPT SMKN 6 Makassar students after treatment. It can be proven that the t-test value is smaller than P (0.000 < 0.05), which means that (H0) of this research is rejected and (H1) is accepted. Therefore, it can be concluded that using fairy tales can improve students' vocabulary abilities. Implications The implication of this study shows that the use of fairy tales in improving the vocabulary of students in class XI UPT SMKN 6 Makassar has a significant impact on improving vocabulary skills. The rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (H1) confirm that the use of fairy tales is effective in improving the students' vocabulary. Thus, the use of fairy tales can be considered as an effective method in improving students' vocabulary.